Pengaruh Kepemimpinan Terhadap Disiplin Kerja Karyawan Yang Dimediasi Employee Engagement - Theresia Vania Priscilla Simanungkalit; Adya Hermawati; Yekti Intyas Rahayu (CV. Ulil Albab Corp, 2024)
The purpose of this study is to evaluate the impact of leadership on work discipline, and also the role of employee engagement as a mediating variable. The research approach used quantitative-explanatory with the population sample used in this study were all permanent employees at Widyagama University Malang. Samples were taken using non-probability techniques and the method used was saturated sampling (census) with a total of 73 respondents. Data were collected using a questionnaire. The data were then processed using Smart Partial Least Square (PLS)-3 software. The results obtained in this study indicate that leadership has a positive but insignificant effect on employee discipline but leadership has a positive and significant effect on employee engagement. While employee engagement has a positive and significant effect on employee work discipline. So it can be seen that employee engagement is able to fully mediate the influence of leadership on employee work discipline at Widyagama University Malang. This shows that if there is an increase in leadership, employee engagement will increase so that employee work discipline will also increase.